Convexity Bias and Perspective Cues in the Reverse-Perspective Illusion - Joshua J. Dobias; Thomas V. Papathomas; Vanja M. Vlajnic (i-Perception, 2016)
The present experiment was designed to examine the roles of painted linear perspective cues, and the convexity bias that are known to influence human observers’ perception of three-dimensional (3D) objects and scenes. Reverse-perspective stimuli were used to elicit a depth-inversion illusion, in which far points on the stimulus appear to be closer than near points and vice versa, with a 2 (Type of stimulus) × 2 (Fixation mark position) design. To study perspective, two types of stimuli were used: a version with painted linear perspective cues and a version with blank (unpainted) surfaces. To examine the role of convexity, two locations were used for the fixation mark: either in a locally convex or a locally concave part of each stimulus (painted and unpainted versions). Results indicated that the reverse-perspective illusion was stronger when the stimulus contained strong perspective cues and when observers fixated a locally concave region within the scene.